Model dan Mekanisme Pengelolaan Kebun Benih Tanaman Hutan Bersertifikat di Perum Perhutani Unit II Jawa Timur dan Puslitbang Perhutani Cepu - BUDI MAJASARI; IM. NARKA TENAYA; IW. BUDIASA (Universitas Udayana, 2013)
The purpose of this research is to find out: (1) the model and mechanism of forest management as the certificated seed nursery forest plant; (2) the model and mechanism of production of the certificated seed nursery forest plant; (3) the model and mechanism of certification of seed nursery, seed, and forest plant seed; and (4) the model and mechanism of forest plant seed and germ marketing at Perum Perhutani Unit II of East Java and Puslitbang Perhutani of Cepu. This research results shows that the mechanism of the certificated seed nursery forest plant management is carried out by maintaining and developing the genetic resources at all working units of Perum Perhutani and the plant glorification is carried out by Puslitbang Perhutani of Cepu. Seed produced is used to produce plant, protected forest rehabilitation and to be marketed. The mechanism of seed and germ production is carried out according to the procedure operational standard. The mechanism of seed nursery, seed and germ of Perum Perhutani is carried out by submitting an application of certification to the Balai Perbenihan Tananamn Hutan Jawa Madura (The Office of Forest Plant Seedling of Java Madura). The mechanism of seed and germ marketing at Perum Perhutani Unit II of East Java is carried out by Kesatuan Bisnis Mandiri (KBM) Agroforestry (Agroforestry Autonomous Business Unit), Puslitbang Perhutani of Cepu, and Kesatuan Pengelolaan Hutan (KPH) (The Forest Management Unit).